Let’s get personal: Which elements elicit perceived personalization in social media advertising? - De Keyzer, Freya; Dens, Nathalie; De Pelsmacker, Patrick (Electronic commerce research and applications, 2022)
•To elicit perceived personalization it is best to use interests, location or age.•Gender, life-events or friend referrals elicit less perceived personalization.•Results remain stable across product perceptions.•Results remain stable across socio-demographic characteristics. On social networking sites, consumers disclose information about themselves which advertisers use to personalize advertisements. The underlying assumption is that personalized advertisements are more persuasive. However, it is not clear to what extent actual personalization elements (as intended by advertisers) determine consumers’ perceptions of the extent to which an ad is personalized, and it is the latter that drives responses. The current study investigates the relative weight of different actual personalization elements (age, gender, location, life events, interests, and friend referrals) in Facebook ads in eliciting perceived advertising personalization. We conduct conjoint analyses for six products (a bank, a smartphone, tableware, furniture, a restaurant, a fashion retailer) with 595 consumers from the United States. The findings show that the most important elements in eliciting perceived personalization are (in order of importance) a person’s interests, location, and age. This result remains stable across different product perceptions (product category involvement, product qualities, and buying motivations) and across different socio-demographic characteristics (gender, age, and education). In sum, to evoke the perception of personalization, advertisers should primarily target consumers based on their interests.